Radical Cystectomy and Lymphadenectomy to Two Patients with Pelvic Kidney: Surgical Pitfalls and Considerations - I. Adamakis; C. Pournaras; I. Katafigiotis; G. Kousournas; E. Fragkiadis; I. Leotsakos; C. Alamanis; D. Mitropoulos; C. Constantinides (Case Reports in Medicine)
Our goal is to describe our experience in the difficulties encountered during radical cystectomy for muscle invasive bladder cancer in patients with contemporary pelvic kidney. Two patients with muscle invasive bladder cancer and contemporary pelvic kidney were subjected to radical cystectomy and extended lymphadenectomy with conversion to an ileal pouch. In both cases, lymphadenectomy was the first step after entering the true pelvis. In order to proceed to the cystoprostatectomy, careful dissection of the ectopic renal vessels and proper mobilization of the kidney were performed. In both cases, an ileal pouch was our choice. The pelvic kidney is the most common sight of renal ectopia. The etiology is the aborted ascent of the fetal kidney from its initial position in the pelvis. This is the first case series describing radical cystectomy for muscle invasive urothelial carcinoma of the bladder in patients with a pelvic kidney.